Carta al editor relacionada con el articulo Satisfacción académica , funcionamiento familiar, apoyo social y estrategias de aprendizaje: Apoyo social y estrategias de aprendizaje como predictores para el estudio de universitrios limeños. - Quiroz Avilés, Mirtha Teresa (2024)
The article presents important findings regarding the influence of academic satisfaction, as well as family, social and strategic variables for achieving the fulfillment of goals and objectives that lead to a successful academic learning process.